Oil revenue and agriculture value-added in oil-exporting countries: does the role of real exchange rate matter - Abdlaziz, Rizgar Abdlkarim; Naseem, N. A. M.; Slesman, Ly (Emerald Publishing, 2022)
Purpose: This study aims to investigate the contingent roles real effective exchange rates (REERs) play in mediating the effects of oil revenue on the agriculture sector value-added in 25 major and minor oil-exporting (MIOEC) countries during the period of 1975–2014. Design/methodology/approach: The panel autoregressive distributed lag (ARDL) estimator proposed by Pesaran et al. (1999) was relied upon to achieve the objectives of the study. This estimator involves a pool of small cross-sectional units over a long-time span that covers for 25 oil-exporting countries over 39 years (1975–2014). Findings: This paper reveals the following findings. Firstly, oil revenue has a direct negative effect on agricultural value-added in the short- and long-term. This finding holds for full sample and subsamples of major oil-exporting (MAOEC) and MIOEC countries. Further assessment reveals that the magnitude of the impact is larger for MAOEC than that of the MIOEC. Secondly, the finding for the long-run effect shows that the contingent effect of real exchange rate on the nexus between oil revenue and agricultural value-added is negative and statistically significant at the conventional level for the full sample. This suggests that, in the long-run, the appreciation in real exchange rates exacerbate the negative marginal effects of oil revenue on agricultural value-added in all oil-exporting countries. However, when sub-samples of MAOEC and MIOEC are considered, the contingent effect disappeared (become insignificant) in MAOEC while it is positive and statistically significant in MIOEC. Thus, in the long-run, the appreciation in real exchange rates diminishes the negative marginal effects of oil revenue on agricultural value-added in MIOEC. While oil revenue has a direct negative effect, its effect is also moderated by the variations in REERs in MIOEC in the long-run. Finally, in the short-run, fluctuations in the real exchange rate do not matter for the nexus of oil revenue and agriculture sector in these countries whether minor or MAOEC countries. Originality/value: This study contributes to the debate in the empirical literature on the Dutch disease effect and “oil curse”. Using the appropriate panel ARDL empirical framework, it provides evidence on how exchange rate variations in the oil-exporting countries influence the nature of the effects of the oil revenue on agricultural sectors in the long-run but not in the short-run. Contingent effects of REERs only appear to exist in MIOEC in the long-run.